An evaluation of drill volumes in Division I women`s lacrosse - Robinson, B.; Thornton, A. R.; Bunn, J. A. (Trends in Sport Sciences, 2022)
Introduction. Monitoring athletes using microtechnology allows for coaches to observe how athletes respond to the physiological demands of training. Aim of Study. The aim of this study was to determine differences in intensities and demand by training mode and position in women`s collegiate lacrosse athletes. Material and Methods. Global positioning systems and heart rate monitors were worn by 27 athletes to gather training volume metrics, including: distance rate, maximum speed distance, high-intensity distance (HID), sprint efforts, accelerations, decelerations, and sprint distance. All data were organized into drill classifications: stickwork (SW), small-sided games (SSG), skill-specific drills (SSD), and simulated game play (SGP). All training metrics, except distance rate and maximum speed, were analyzed per minute spent in the drill to control for time. The drill database consisted of 99 days of training, which included three drills for SW, four drills for SSD, five drills for SSG, and five drills for SGP. Results. There was no difference in training workload by position (p = 0.414), but there was a difference in workload by drill type (p < 0.001), and an interaction between drill type and position (p = 0.031). For distance and accelerations, SSD was less than all other types of drills (p < 0.001 for all), and SSD had fewer decelerations than SSG (p = 0.011). SW drills registered less HID and fewer decelerations than all other types of drills (p < 0.001), and fewer sprint repetitions, accelerations, and less sprint distance than SSG (p = 0.001-0.011) and SGP (p = 0.001- -0.013). Conclusions. Coaches can use this information to provide more specific training for each position and to manage the training volume of their athletes. Drill intensities can also be compared to game intensities to provide more specific training for games.